Prosthodontic management of a completely edentulous microstomia patient - Chiramana Sandeep; O. Swetha Hima Bindu; B. Sreedevi; K. Sai Prasad (Wolters Kluwer Medknow Publications, 2014)
Prosthodontic management of a completely edentulous patient with microstomia is challenging for both the operator and the patient. Limited mouth opening can be caused by the head and neck radiation, surgically treated head and neck tumors, connective tissue diseases, facial burns, reconstructive lip surgeries and the most common factor oral submucous fibrosis. It is often difficult to apply conventional clinical procedures to construct dentures for patients who demonstrate limited mouth opening, as it is difficult to insert or remove the custom trays, denture bases and the final prosthesis is in one piece because of the constricted opening of the oral cavity. However, with careful treatment planning and designing, many of the apparent clinical difficulties can be overcome. This article deals with a case report of treatment procedure and sectional prosthesis design for a patient with microstomia. All the procedures were intended for better function, health, esthetics and overall well-being of the patient.